2021
DOI: 10.1016/j.celrep.2021.109237
|View full text |Cite
|
Sign up to set email alerts
|

Stress granules inhibit fatty acid oxidation by modulating mitochondrial permeability

Abstract: Summary The formation of stress granules (SGs) is an essential aspect of the cellular response to many kinds of stress, but its adaptive role is far from clear. SG dysfunction is implicated in aging-onset neurodegenerative diseases, prompting interest in their physiological function. Here, we report that during starvation stress, SGs interact with mitochondria and regulate metabolic remodeling. We show that SG formation leads to a downregulation of fatty acid β-oxidation (FAO) through the modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 124 publications
(191 reference statements)
0
29
0
Order By: Relevance
“…Notably, levels of oxidative stress were similar between fasted cPPAR -/hearts and control hearts. This also indicates that the change in Plin2 does not appear to be associated with the deleterious results that have been reported in some models where lipid storage is dysregulated [18,56,62,63]. It will be interesting in the future to investigate how specific lipids (including DAGs and ceramides) are different between cPPAR -/hearts and control hearts.…”
Section: Plos Onementioning
confidence: 79%
See 1 more Smart Citation
“…Notably, levels of oxidative stress were similar between fasted cPPAR -/hearts and control hearts. This also indicates that the change in Plin2 does not appear to be associated with the deleterious results that have been reported in some models where lipid storage is dysregulated [18,56,62,63]. It will be interesting in the future to investigate how specific lipids (including DAGs and ceramides) are different between cPPAR -/hearts and control hearts.…”
Section: Plos Onementioning
confidence: 79%
“…Changes in Plin have been linked to changes in oxidative stress and cardiac dysfunction [18,56,62,63]. In particular, a rise in the lipid species diacylglycerol (DAG) and ceramides have been linked to cardiac lipotoxicity [64][65][66][67].…”
Section: Plos Onementioning
confidence: 99%
“…The formation dynamics of SG under arsenite vs. resveratrol conditions was similar in HEK293T cells, plateauing at 30–40 min of the treatment, except for the difference in the average size of the resulting granules, explained by a higher proportions of smaller initiating clusters under resveratrol and piceatannol conditions ( Figure 2, D and E ). Next, we measured the internal dynamics of resveratrol and arsenite SGs, using an endogenously tagged PABPC1-Dendra2 cell line ( Amen and Kaganovich, 2020b , 2021 ). Dendra2 is a photoconvertible fluorescent protein ( Gurskaya et al.…”
Section: Resultsmentioning
confidence: 99%
“…, 2018b ; Amen and Kaganovich, 2020d ). For example, we recently showed that SGs form on mitochondria during prolonged starvation stress and inhibit the import of fatty acids for fatty acid oxidation ( Amen and Kaganovich, 2021 ). Because SGs formed through other pathways nevertheless have an inhibitory effect on fatty acid oxidation, the SG lifetime as determined by clearance kinetics will have a profound impact on cell metabolism ( Amen and Kaganovich, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This includes the pro-apoptotic proteins RACK1 (Arimoto et al, 2008), TRAF2 (Kim et al, 2005), RhoA-Rock1 complex (Tsai and Wei, 2010), YWHAX (Zhao et al ., 2021), BAX (Zhao et al ., 2021), and mTORC1 constituents (Thedieck et al, 2013; Wippich et al, 2013). Another common theme is that stress granules may also promote cell survival by reducing reactive oxygen species in cells through a variety of mechanisms (Amen and Kaganovich, 2021; Takahashi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%